1990
DOI: 10.1902/jop.1990.61.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Analysis of Actinobacillus actinomycetemcomitans Epidemiology

Abstract: Research over the past decade has identified many of the microorganisms involved in the etiology of human periodontitis such as Actinobacillus actinomycetemcomitans. Efforts are now directed toward defining these species' role in the pathogenic process. Since microbial colonization of host tissues is a key first step in developing a bacterial infection, determining the source of the periodontal pathogens and their route of transmission is likely to be crucial in formulating preventive strategies. Recently, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
2

Year Published

1991
1991
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 19 publications
1
31
2
2
Order By: Relevance
“…They found 2 genotypes in 8 patient isolates and minor differences in 7 reference strains. Recently Zambón et al 26 reported the existence of three major restrictions patterns within 124 A. actinomycetemcomitans isolates. In the present study 9 different patterns were obtained from 11 independent isolates of A actinomycetemcomitans.…”
Section: Discussionmentioning
confidence: 99%
“…They found 2 genotypes in 8 patient isolates and minor differences in 7 reference strains. Recently Zambón et al 26 reported the existence of three major restrictions patterns within 124 A. actinomycetemcomitans isolates. In the present study 9 different patterns were obtained from 11 independent isolates of A actinomycetemcomitans.…”
Section: Discussionmentioning
confidence: 99%
“…actinomycetemcomitans has several serotypes, and it appears that the presence of the LT determines virulence (105). Serotype b strains are most often LT ϩ , and significantly higher proportions of LT ϩ isolates are found in diseased patients than in healthy individuals (343). Highly leukotoxic strains were found only in subjects with LJP and EOP and tended to colonize younger individuals (105).…”
Section: Specific Plaque Hypothesismentioning
confidence: 99%
“…In general, all these methods show heterogeneity within the species A. actinomycetemcomitans (13)(14)(15)(16)(17)(18)(19)(20)(21). However, in these methods not all independent isolates can be distinguished from each other.…”
Section: Discussionmentioning
confidence: 99%